Case Report: Rabies Vaccine-Induced Thrombotic Thrombocytopenic Purpura in a Patient With Systemic Lupus Erythematosus - Cui, Yanming; Wei, Jianbo; Peng, Xiang (Frontiers in Immunology, 2022)
For patients with autoimmune diseases, vaccination is controversial. The use of vaccination in patients with autoimmune diseases is controversial. There are many reports of secondary thrombotic thrombocytopenic purpura cases after various vaccinations. Thrombotic thrombocytopenic purpura is a rare thrombotic microangiopathy characterized by microvascular pathological hemolytic anemia, severe thrombocytopenia, and ischemic organ damage with a very high fatality rate. We report a case of thrombotic thrombocytopenic purpura in a patient with systemic lupus erythematosus after rabies vaccination. She developed gastrointestinal bleeding nearly a month after the vaccination. Laboratory tests confirmed a severe deficiency of ADAMTS13 and the presence of ADAMTS13 autoantibodies. Through early identification of thrombotic thrombocytopenic purpura, immunosuppressive therapy, and plasma exchange treatment, the patient was saved from danger. This case suggests that attenuated vaccines may also have unexpected adverse effects in patients with long-term use of immunosuppressive drugs and autoimmune diseases. To our knowledge, this is the first case report of thrombotic thrombocytopenic purpura in a patient with systemic lupus erythematosus secondary to rabies vaccination.